Leaf epidermal studies of four species of Chlorophytum Ker- Gawl in Nigeria - BS Omokanye; OT Mustapha; AA Abdulrahaman; OS Kolawole (Journal of Applied Sciences and Environmental Management, 2021)
Studies of the foliar epidermal morphology in four species of Chlorophytum; C. orchidastrum, C. bichetii, C. stenopetalum and C. macrophyllum revealed the presence of stomata on both sides of the leaves (amphistomatic stomata distribution). In C. orchidastrum, few stomata are present on the adaxial surfaces. Stomata type has no diagnostic importance as all the species studied have tetracytic stomata. Stomata index (<10%) on the adaxial surface in C. orchidastrum easily distinguished the species from others. In C. bichetii and C. macrophyllum stomata index (<50%) was recorded while stomata index (>50%) was recorded for C. stenopetalum on the adaxial surface. Stomata index on the abaxial surface also shows that fewer stomata occur in C. macrophyllum compared with C. stenopetalum. The studies also revealed smooth leaf margin for C. orchidastrum. Papillea out growth were observed on the leaf margin of C. stenopetalum and C. macrophyllum, Papillea projections were however more pronounced in C. bichetii. Leaf epidermal character is hereby indicated as an important tool in delimiting species in the genus Chlorophytum.